Criptosporidiose em crianças de 2 anos de idade com diarréia aguda em Belém, Pará, Brasil - Loureiro, Edvaldo Carlos Brito (1989)
Cryptosporidiosis in children (1-2 years old) with acute diarrhoea from Belém, Pará, Brazil - Two hundred-and one samples obtained from 61 children were examined for Cryptosporidium infection during a period of 12 months. One hundred fifteen specimens were collected during diarrhoea episodes and lhe remainillg 86 obtained out of diarrhoea period, as contrais. A// samples were examined by a modified Ziehl-Neelsen staining method. Cryptosporidium was detected in 6 (5.2%) of 115 samples from diarrhoeic children. A// nondiarrhoeic contrai patients were nega tive for Cryptosporidium. The present study suggests that Cryptosporidium is an agent of self-limited diarrhoea among immunocompetent children from Belém, Pará.